Elucidating functional interactions between the Russian wheat aphid (D. noxia Kurjumov) and bread wheat (Triticum aestivum L.) - Schultz, Thia (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2014.